2004
DOI: 10.1111/j.1365-2265.2004.02196.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of long‐term cardiovascular, neurological and psychosocial morbidity after treatment for craniopharyngioma

Abstract: Craniopharyngioma is associated with excessive long-term multisystem morbidity and mortality, especially in female patients, despite a high cure rate. These observations indicate that dedicated long-term follow-up of these patients is required. The purpose of the follow-up should be: first, to look for recurrences and to ensure appropriate endocrine replacement, especially oestrogen replacement in premenopausal females; and second, to achieve intensive control of glucose, lipids, blood pressure and weight, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
159
2
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 32 publications
10
159
2
5
Order By: Relevance
“…The role of sex as a prognostic factor is not established; some authors report a higher mortality among females (28,29), but others have not found any sex differences (13,15,16). One of the two studies reporting higher mortality rates in females suggested a possible role of estrogen deficiency (29), but the other study did not consider that unsupplemented gonadal insufficiency had a significant impact on enhanced mortality (28).…”
Section: European Journal Of Endocrinologymentioning
confidence: 84%
See 2 more Smart Citations
“…The role of sex as a prognostic factor is not established; some authors report a higher mortality among females (28,29), but others have not found any sex differences (13,15,16). One of the two studies reporting higher mortality rates in females suggested a possible role of estrogen deficiency (29), but the other study did not consider that unsupplemented gonadal insufficiency had a significant impact on enhanced mortality (28).…”
Section: European Journal Of Endocrinologymentioning
confidence: 84%
“…The OS rates (which reflect effect of multiple treatments) described in an exclusively pediatric series ranged from 83 to 96% at 5 years (14, 15, 17, 30, 31, 32, 33) and 65 to 100% at 10 years (15, 26, 30, 31, 32, 34, 35, 36, 37, 38, 39, 40, 41), averaging 62% at 20 years (42). In adults or a broad age-range population (adults and children) series, the OS rates ranged from 54 to 96% at 5 years (13,16,25,29,32,43,44,45,46), 40 to 93% at 10 years (13,16,25,28,29,32,43,44,45,46), and 66 to 85% at 20 years (29,45,46). The lower limits of survival rates usually reflected data from earlier series that occurred before modern advances in microsurgery, neuroimaging, and radiotherapy.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the propensity for local recurrence of the tumour, more extensive and/or multiple surgeries and/or radiotherapy is frequently advocated, which often results in hypothalamic-pituitary dysfunction in these patients. Hypothalamic damage has been implicated as the main risk factor for obesity in patients with COCP (7), and the increased cardiovascular risk and poor QoL have been reported to be related to both obesity and GHD (3,8) in these patients. In addition, GHD due to COCP has been reported to increase the risk of metabolic syndrome (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although histologically benign, most patients with craniopharyngiomas (85-90%) have significant pituitary hormone deficits (2, 3) with growth hormone (GH) deficiency (GHD) being the most common (54-100%) (4), and have decreased quality of life (QoL) with significant psychosocial and neurocognitive impairment (3). Previous studies have reported that patients with craniopharyngiomas not only have three-to fivefold higher morbidity and mortality rates compared with the general population (3,5), but also have higher morbidity and mortality rates compared with patients with other causes of hypopituitarism, namely those with non-functioning pituitary adenomas (6).…”
Section: Introductionmentioning
confidence: 99%